2019
DOI: 10.1111/tmi.13352
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloidiasis screening in migrants living in Spain: systematic review and meta‐analysis

Abstract: Objectives To provide information regarding the prevalence of strongyloidiasis among migrants coming from Strongyloides stercoralis‐endemic areas who reside in Spain. Methods Systematic review of the literature and meta‐analysis of studies showing prevalence of S. stercoralis infection among migrants from Latin America, Africa, Eastern Europe, Asia and Oceania who reside in Spain. We included articles published until 30 April 2019 without language restriction. The keywords used for the search included ‘Strongy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
(84 reference statements)
3
9
0
Order By: Relevance
“…These clinical and laboratory findings are consistent with other studies [ 20 ] showing that eosinophilia is a good correlator of the infection. Sociodemographic characteristics such as age, sex and country of origin are in accordance with those found in our non-community migrant population [ 21 ], except for a slightly higher presence of men, which might reflect the occupational nature of the infection [ 22 ]. On the other hand, we also found a weak association with the geographical area of origin being that the infection was more frequently reported in individuals coming from Latin American countries.…”
Section: Discussionsupporting
confidence: 85%
“…These clinical and laboratory findings are consistent with other studies [ 20 ] showing that eosinophilia is a good correlator of the infection. Sociodemographic characteristics such as age, sex and country of origin are in accordance with those found in our non-community migrant population [ 21 ], except for a slightly higher presence of men, which might reflect the occupational nature of the infection [ 22 ]. On the other hand, we also found a weak association with the geographical area of origin being that the infection was more frequently reported in individuals coming from Latin American countries.…”
Section: Discussionsupporting
confidence: 85%
“…A recent review of the literature showed a prevalence of S. stercoralis infection ranging from 10% to 20% in immigrant population living in Spain. These data support the active screening of populations coming from endemic areas given the potential risk of serious presentation in situations of immunosuppression [ 10 ]. The frequency of this parasitosis and its potentially deleterious consequences has led the European Center for Disease Control to include strongyloidiasis in the routine screening of migrants coming from endemic areas [ 11 ].…”
Section: Introductionsupporting
confidence: 69%
“…S. stercoralis infection is estimated to have a prevalence of between 7% and 40% among migrants, depending on the survey and patients’ country of origin [ 14 , 29 ]. In a recent meta-analysis of the prevalence of strongyloidiasis in migrants from endemic areas who reside in Spain, the authors found an overall prevalence of 14% in Latin Americans [ 30 ]. Our study showed a lower prevalence than that (6% in children and adolescents and 12% in adults; 11% overall), but a similar proportion as another study performed in Spain, where the prevalence was 10.9% in patients from South America [ 3 ].…”
Section: Discussionmentioning
confidence: 99%